2013
DOI: 10.1016/j.ydbio.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Drosophila A-type lamin C initially causes tendon abnormality including disintegration of cytoskeleton and nuclear lamina in muscular defects

Abstract: a b s t r a c tLamins are the major components of nuclear envelope architecture, being required for both the structural and informational roles of the nuclei. Mutations of lamins cause a spectrum of diseases in humans, including muscular dystrophy. We report here that the loss of the A-type lamin gene, lamin C in Drosophila resulted in pupal metamorphic lethality caused by tendon defects, matching the characteristics of human A-type lamin revealed by Emery-Dreifuss muscular dystrophy (EDMD). In tendon cells la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 56 publications
3
19
0
Order By: Relevance
“…The limited number of available human samples and inherent genomic heterogeneity, however, limits the conclusions that can be made. Our results are consistent with previous reports of NE damage and intrusion of cytoplasmic organelles into the nucleoplasm in skeletal muscle fibers of patients with EDMD [64][65][66][67] , cardiac myocytes in LMNA-dilated cardiomyopathy patients 68,69 , lamin A/Cdeficient mice 13,70 , and muscle and tendons of lamin-deficient fruit flies 71,72 . Unlike those previous reports, however, we now provide detailed information on the extent, timing, and cause of the NE damage, revealing a striking correlation of NE rupture and disease severity.…”
Section: Discussionsupporting
confidence: 93%
“…The limited number of available human samples and inherent genomic heterogeneity, however, limits the conclusions that can be made. Our results are consistent with previous reports of NE damage and intrusion of cytoplasmic organelles into the nucleoplasm in skeletal muscle fibers of patients with EDMD [64][65][66][67] , cardiac myocytes in LMNA-dilated cardiomyopathy patients 68,69 , lamin A/Cdeficient mice 13,70 , and muscle and tendons of lamin-deficient fruit flies 71,72 . Unlike those previous reports, however, we now provide detailed information on the extent, timing, and cause of the NE damage, revealing a striking correlation of NE rupture and disease severity.…”
Section: Discussionsupporting
confidence: 93%
“…Remarkably, the critical function of lamin C is exerted in tendon cells, not muscle, and involves the spectraplakin-dependent stabilization of the cytoskeleton (Uchino et al, 2013). Mammalian tendons are maintained by fibroblasts, which actively migrate and proliferate in response to injury (Arnesen & Lawson, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest Lmo7 activity is regulated by p130Cas-dependent association with focal adhesions. These findings are discussed in the light of a Drosophila study that showed A-type lamins exert their critical function in tendon cells (Uchino et al, 2013), which connect to muscle cells via the extracellular matrix, and evidence that integrin-dependent signaling is important for cells to respond to and withstand mechanical stress (Pines et al, 2012). …”
Section: Introductionmentioning
confidence: 98%
“…Drosophila lamin C, which is the homolog of mammalian A/C type lamin, displays tissuespecific expression levels in fully differentiated cells 39,40 . Mutations in lamin A/C have been associated with aberrant chromatin organization and global detachment of chromatin from the nuclear lamina in a wide range of model organisms and tissues 15,18,19 .…”
Section: Lamin C Over-expression Disrupts Chromatin Localization At Tmentioning
confidence: 99%